DEVELOPMENT OF FOURTH INDUSTRY ORIENTED MECHANICAL ENGINEERING MECHATRONICS LEARNING DEVICES 4.0 - Hamid, Hefri; Jalinus, Nizwardi; Inra, Azwar; Ambiyar, Ambiyar; Waskito, Waskito; Sukardi, Sukardi; Herlin, Niny (LPPM Undiksha, 2019)
The ability of modern industrial work must be mastered by vocational engineering students, therefore it is important to develop learning tools that are oriented to the fourth industry. This study assesses the development of mechatronics learning tools that are arranged based on the abilities that must be possessed by students to work in the fourth industrial era using the IDI model. Data was collected from the validity, practicality and effectiveness tests on the programmed subjects in 2019. Learning activities carried out during 16 meetings to produce a smart factory (prototype). Analysis shows that learning tools are developedit is valid, then the response of teaching staff shows the criteria are very practical and based on the response of students also in the category of very practical. The findings, an increase in students' understanding of the value of the end of the semester, but they have to struggle even more to obtain more optimal results. Besides, the learning device also forms the general ability of the learner, the learning communicative, collaborative, innovative, creative, leadership and entrepreneurship that observed during the process of learning to walk